2016
DOI: 10.5539/jfr.v5n2p67
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Proximate and Anti-nutritional Composition of African yam bean (Sphenostylis stenocarpa) Seeds Varieties

Abstract: The physical, proximate and anti-nutritional properties of five accessions of African yam bean (AYB) seeds (TSs 57, TSs 61, TSs 93, TSs 94 and TSs 116) obtained from Genetic Resource Centre (GRC) of International Institute of Tropical Agriculture (IITA) were studied and compared. This was aimed at unraveling the nutritional importance of this crop to enhance its production and utilisation. The physical properties investigated include seed size, length to diameter ratio, seed weight, percentage of seed coat, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 12 publications
2
26
3
Order By: Relevance
“…Tannins have been described to have cross-linked with proteins and caused a reduction in in vitro protein digestion of beans [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Tannins have been described to have cross-linked with proteins and caused a reduction in in vitro protein digestion of beans [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors including different seed accession, planting location, agronomic practices as well as seasons of the year when the bean was planted may influence their proximate composition. Some authors have studied different variants of AYB and reported slight differences in protein content 22.33-25.78% (Adeyeye et al, 1994), 22.72-26.68% (Ajibola and Olapade, 2016) 21.84-23.41% (Baiyeri et al, 2018).…”
Section: Proximate and Nutritional Composition Of African Yam Beanmentioning
confidence: 99%
“…Over the years, there have been limitations to the use of many African legumes, due to certain attributes that have been associated with them. The two most important limitations that have been discussed by different authors for many years are their hard-to-cook nature ( Ojo and Ade-omowaye, 2015 ; Duodu and Apea-Bah, 2017 ; Maphosa and Jideani, 2017 ) and the presence of non-nutritional compounds otherwise known as anti-nutrients ( Prasad and Singh, 2015 ; Ajibola and Olapade, 2016 ; Duodu and Apea-Bah, 2017 ). African yam bean is one of many leguminous crops that exhibit these limitations.…”
Section: Limitations To the Use Of African Yam Beanmentioning
confidence: 99%
See 2 more Smart Citations